PENGEMBANGAN E-KOMIK BERBASIS NILAI-NILAI AL-ISLAM DAN BUDAYA INDONESIA PADA SISWA RUMAISA SCHOOL KOREA SELATAN - Mukhlishina, Innany; Wijayaningputri, Arinta Rezty; Danawati, Murtyas Galuh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The development of technology-based education is increasingly rapid, making it mandatory for the world of education to be able to master technology. Technology is developing so rapidly that digital media has become a new medium for producing e-comics. The results of interviews with the principal of Rumaisa School show that Rumaisa School's learning is based on Al-Islamic values. Rumaisa School students need an introduction to Indonesian culture so that a sense of nationalism continues to grow within students. The learning media that can be used by teachers to internalize the values of Al-Islam and Indonesian culture to students is e-comics. The aim of this research is to develop e-comics based on Islamic values and Indonesian culture that are valid and interesting. The development model used is ADDIE (Analyze, Design, Development, Implementation, Evaluation). Data collection techniques use interview and questionnaire techniques. The instruments for this research include interview sheets, validation questionnaires, and student response questionnaires. Data analysis techniques include media validity analysis and media attractiveness analysis. The e-comic product was developed in the form of a flipbook. E-Comics have been validated by material experts and media experts. The material expert validation results obtained 91.6% with valid criteria. Furthermore, the media expert validation results obtained 72% with valid criteria with revisions. After the e-comic revision, a second media expert validation was carried out. Media expert validation results were 92% with valid criteria. After completing validation, the e-comic product was implemented on Rumaisa School South Korean students. Based on the student response questionnaire, students got 83% with interesting criteria. The development of e-comics based on AL-Islamic values and Indonesian culture is valid and interesting to use for learning for Rumaisa School students in South Korea.